Successfully navigating the paradox of control and autonomy in succession: The role of managing ambivalent emotions. (May 2020) - Radu-Lefebvre, Miruna; Randerson, Kathleen
This article theorises how, why and with what outcomes successors manage the paradox of control and autonomy emerging as role conflict through emotion management strategies; thus, it contributes to theory building on paradox and emotion management in family business. Drawing on 20 interpretive case studies of French family businesses operating in wide-ranging industries, we highlight emotional ambivalence towards the father/incumbent, the mother, siblings and cousins, and leadership and document their prevalence in enmeshed family businesses. We show that when motivated by self-conformity and self-protection motives, successors accept the incumbent's control and manage ambivalent emotions through defensive strategies, such as avoidance or compromise, which contributes to the pursuit of successor legitimacy. We reveal that during successor installation, successors might reject the incumbent's control and instead promote personal autonomy by managing ambivalent emotions through confrontational strategies, such as hyperbolised emotional reactions, emotional display of negative emotions or holism, which contributes to successor emancipation.